Globalization and Exclusion of Marginalized Sections of the Society: An Indian Experience: - Mahmood, Faisal (Society & Sustainability, 2021)
While globalization has accelerated the flow and interconnectedness of capital, goods, information, people, and technology, it has also intensified disconnection, exclusion, and marginalization. Much research has been undertaken on this subject, aimed primarily at providing the bases for the policies for eradication of the exclusionary process of globalization. This paper, based on secondary data, seeks to add to this body of knowledge by addressing the following issues. First, it tries to explain the concept of globalization and how it has affected India. Also, it highlights how the exclusionary processes associated with globalization have provided ways for social exclusion. The data used in this paper are extracted from the carefully selected literature on the subject. It has examined the link between globalization and the exclusion of marginalized sections in India. The findings of this paper show how globalization touches upon issues of well-being and social justice. In the process of globalization-driven development, marginalized sections have paid their toll in the form of their land, livelihood, culture, knowledge, and other resources. In the name of development, governments have put the lives of these groups at stake, especially tribals. This study recommends a few measures to minimize the widening gap between the weaker and the dominants that would be helpful for policymakers in minimizing the exclusionary practices led by globalization towards the marginalized sections.